The The Role of Breast Sonography and Ductography in the Evaluation of Different Causes of the Nipple Discharge - Al-Ani, Ahlam J Kalaf (AL-Kindy College Medical Journal, 2019)
ABSTRACT Background : The aim of this work is to assess the role of breast sonography  and ductography in the evaluation of different causes of nipple discharge.Methods :  The study will be carried out on twenty-five female patients referred to the Radiodiagnosis department at Alexandria Main University Hospital presenting with nipple discharge.They were divided into two groups:Group I include 10 patients (40%) with surgically significant nipple discharge who were the patients with unilateral, uniorificial surgically significant colour type nipple discharge .They were investigated by mammography, sonography, and ductography.Group II include 15 patients (60%) with surgically insignificant nipple discharge. They were further subdivided into 9 patients (36%) with unilateral multiorificial and 6 patients (24%) with bilateral nipple discharge. They were subjected to mammography ,sonography without ductography.Results Nipple discharge is the release of fluid from the nipple. It is the third most common breast complaint for women seek medical attention, after lumps and breast pain. It is a symptomatic problem that causes many women both discomfort and anxiety.  Conclusion : The current study showed certain diagnostic sonographic features for patients of multiple papillomatosis was agreed with studies carried outKey words : Breast, Ductography, Nipple Corresponding address to :Dr. Ahlam Jamil  Al-Ani m.b.b.ch. Al- Faloja Hospital